(untitled) (Research, Society and Development, 2022)
Introduction: Prechtl’s method presents itself as a great ally in the early identification of neurological sequelae through the General Movements Assessment – GMA. Objective: to verify the association between GMA and risk factors for delay neuropsychomotor development (NPMD). Method: cross-sectional study carried out in the neonatal ICU, with children younger than 37 weeks, of both sexes, without metabolic disorders, peripheral nerve injuries, congenital malformations or cardiac abnormalities. Data were collected through GMA and associated with risk factors for NPMD, a significance level of 5% was admitted. Results: 44 premature infants (mean age 30.9 ± 3.4 weeks; 28 [63.6%] female were analyzed. The associations indicated: prematurity (OR: 3.42; CI: 0.55-21.17), low birth weight (OR: 2.75; CI: 0.44-16.89), neonatal hypoxia (OR: 0.20; CI: 0.03-1.27), hyperbilirubinemia (OR: 3.84; CI: 0.62-23.85), respiratory distress syndrome (OR: 1.37; CI: 0.24-7.71), sepsis (OR: 1.70; CI: 0.15-18.44), smoking (OR: 0.75; CI: 0.07-7.89), alcohol use (OR: 1.12; CI: 0.11-11.2), urinary tract infection (OR: 0.26; CI: 0.04-1.61) and gestational anemia (OR: 2.03; CI: 0.21-19.49) Conclusion: there was no association between neonatal and obstetric risk factors with General Movements.